Comparative study of the elemental composition of leaves of common lilac varieties amethyst and Nadia - Popyk, Andrii; Iosypenko , Olena; Novosel , Olena (Annals of Mechnikov's Institute, 2026)
Introduction. Macro- and microelements are important and valuable components of the general homeostatic system of the human body, which are vital for regulating the activity of all organs and systems. The functional significance and biological value of macro- and microelements is manifested at all levels of life: cellular, molecular, subcellular, tissue, and also at the level of the whole organism. They ensure the activation of most of the body's enzyme systems, promote the stimulation of tissue respiration processes, activate energy metabolism and hematopoiesis processes, influence immune responses, the synthesis of biologically active compounds and various hormones, metabolism of proteins, lipids, nucleic acids, carbohydrates, and correct various free radical processes in the human body. The most valuable elements are sodium, potassium, calcium, magnesium, iron, zinc, and phosphorus. Sodium is necessary for the transport of amino acids and glucose to the body's cells, maintains osmotic balance in cells, and ensures a stable blood pH level, nerve impulse conduction, and heart muscle contraction. Potassium is equally important, as it regulates and maintains normal blood pressure and supports a stable heart rhythm. Potassium plays an important role in various physiological reactions, and its deficiency or excessive concentration can affect human health. Calcium activates enzymes such as pancreatic lipase and the synthesis of the neurotransmitter acetylcholine. Magnesium is important for enzymatic reactions in the human body and the metabolism of nutrients. It ensures the transmission of nerve impulses and maintains a constant body temperature. Due to its ability to form reversible chelate-like bonds with organic substances, magnesium ensures the course of numerous biochemical reactions. Mg2+ is an intracellular cation, second in abundance only to K+, and is found mainly in mitochondria, the nucleus, and ribosomes. Up to 90% of intracellular Mg2+ is bound to ATP, so ATP levels are one of the main factors limiting its reserves. Mg2+ ions are part of 13 metalloproteins and over 300 enzymes. Mg2+ performs a number of important functions in the body: it participates in the synthesis of nucleic acids and proteins, promotes the formation of fats (synthesis of lipoprotein complexes on ribosomes), and regulates the balance of triacylglycerols and high- and low-density lipoproteins. Ferrum is an essential component of myoglobin, hemoglobin, and a number of enzymes that play an important role in the oxidation of red blood cells, as well as ensuring the functioning of the nervous system and preventing the development of anemia in the body. Zinc ensures the stable activity of various enzymes (carbonic anhydrase, RNA polymerase, alcohol dehydrogenase, and alkenyl phosphatase). A lack of zinc in the diet can be the main cause of delayed puberty, hair loss, impaired wound healing, and emotional disorders. Phosphorus is one of the most important elements responsible for fetal development, sperm production, and proper immune response, and is also a component of more than 240 enzymes. A significant phosphorus deficiency in the body is accompanied by complex dysfunction of all organs and systems. In the human body, depending on their quantity, all elements are conditionally divided into macronutrients (Cl, P, Mg, K, Na, Ca), whose quantitative content ranges from 10% to 0.001% of body weight, and microelements (Ge, B, Cr, Sn, Zn, F, I, Co, Si, Li, Mn, Cu, Mo, Ni, Se, V, Fe), whose concentration ranges from 0.001% to 0.000001% of body weight. Macro- and microelements, without which various physiological processes in the body are impossible, are called essential (calcium, selenium, zinc, iron, chromium, copper, iodine, manganese, molybdenum, cobalt). That is why the search for new plant sources promising in terms of macro- and microelement content is a relevant direction of phytochemical research. Common lilac and its varieties cultivated in Ukraine can be rich in various elements, as they contain valuable biologically active compounds (iridoids, lignans, flavonoids, tannins, eleutherosides, essential oil, etc.). The aim of the study is to investigate the macro- and microelement composition of leaves of common lilac varieties Amethyst and Nadia to determine their potential as sources of macro- and microelements. Materials and methods. The object of the study was the leaves of common lilac varieties Amethyst and Nada, harvested in the botanical garden of the National University of Pharmacy, dried by convection and powdered. The obtained powders were used to determine the qualitative composition and quantitative content of mineral compounds by atomic absorption spectroscopy. Results and discussion. The leaves of common lilac varieties Amethyst and Nadia contain 18 macro- and microelements, dominated by potassium (3330.00-3200.00 μg/100 g), magnesium (550.00-500.00 μg/100 g), calcium (1000.00–985.00 μg/100 g), and silicon (440.00-400.0 μg/100 g). Among the microelements in the studied varieties of common lilac, nickel (0.45-0.30 μg/100 g), molybdenum, and lead (<0.03 μg/100 g) were found in the smallest amounts. The concentration of heavy metals such as cobalt, cadmium, arsenic, and mercury was within the maximum permissible limits, which fully complies with the requirements of the State Pharmacopoeia of Ukraine for plant raw materials. Conclusions. The content of micro- and macroelements in the leaves of common lilac varieties Amethyst and Nadia was studied using atomic emission spectroscopy. The raw material studied showed an accumulation of 18 elements, which varied slightly in terms of quantitative content, with a predominance in the leaves of the Amethyst variety. In terms of content, potassium, magnesium, calcium, and silicon predominated in both varieties studied. Given that potassium accounted for more than 50% of the total mineral content, common lilac leaves can be used as a promising source of medicinal products for the prevention and treatment of cardiovascular diseases.